What Is the Arrhythmic Substrate in Viral Myocarditis? Insights from Clinical and Animal Studies - Tse, Gary; Yeo, Jie M.; Chan, Yin Wah; Lai, Eric T. H. Lai; Yan, Bryan P. (Frontiers in Physiology, 2016)
Sudden cardiac death (SCD) remains an unsolved problem in the 21st century. It is often due to rapid onset, ventricular arrhythmias caused by a number of different clinical conditions. A proportion of SCD patients have identifiable diseases such as cardiomyopathies, but for others, the causes are unknown. Viral myocarditis is becoming increasingly recognized as a contributor to unexplained mortality, and is thought to be a major cause of SCD in the first two decades of life. Myocardial inflammation, ion channel dysfunction, electrophysiological and structural remodeling may play important roles in generating life-threatening arrhythmias. The aim of this review article is to examine the electrophysiology of action potential conduction and repolarization and the mechanisms by which their derangements lead to triggered and reentrant arrhythmogenesis. By synthesizing experimental evidence from pre-clinical and clinical studies, a framework of how host (inflammation) and viral (altered cellular signaling) factors can induce ion electrophysiological and structural remodelling is illustrated. Current pharmacological options are mainly supportive, which may be accompanied by mechanical circulatory support. Heart transplantation is the only curative option in the worst case scenario. Future strategies for the management of viral myocarditis are discussed.